1979
DOI: 10.1055/s-0039-1687208
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Plasma Levels of β-Thromboglobulin and Platelet Factor 4 in Various Diseases

Abstract: Contentrations of β-thromboglobulin (β-TG) and platelet factor 4 (PF-4) in platelet poor plasma were determined using radioimmunoassay in 97 healthy subjects and 307 hospitalized patients. In normal subjects, mean values (and SEM) of β-TG and PF-4 were 37±2 ng/ml and 8.3+1.5 ng/ml, respectively. Levels of β-TG increased with age. A statistically significant correlation between concentrations of β-TG and PF-4 was observed in 30 normal subjects (r=0.77, p<0.001). Levels of these protein increased in cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

1981
1981
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…As for the interpretation of the results of this study, two facets of the cold pressor tests should be considered: the autonomic function and the response to stress. PF4 is generally accepted as being a biochemical marker of platelet activity in vivo, as is ß-thromboglobulin (BTG) (28,29). The biological half time of these compounds differs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the interpretation of the results of this study, two facets of the cold pressor tests should be considered: the autonomic function and the response to stress. PF4 is generally accepted as being a biochemical marker of platelet activity in vivo, as is ß-thromboglobulin (BTG) (28,29). The biological half time of these compounds differs.…”
Section: Discussionmentioning
confidence: 99%
“…The PPP samples were frozen at -70°C until the assay. The PF4 levels in PPP samples were estimated by radioimmunoassay (28,29) using PF4-RIAKIT (Dainabot Co. Ltd., Japan).…”
Section: Methodsmentioning
confidence: 99%
“…PF4 is generally accepted as being a biochemical marker of platelet activity in vivo, as is /3-thromboglobulin (BTG) (28,29). On the other hand, the cold pressor test contains some elements of stress.…”
Section: Discussionmentioning
confidence: 99%
“…The PF4 levels in PPP samples were estimated by radioimmunoassay (28,29) using PF4-RIAKIT (Dainabot Co. Ltd., Japan). Normal saline without heparin was slowly infused.…”
Section: Methodsmentioning
confidence: 99%
“…Increased platelet turnover and decreased platelet survival is usual in patients with DIC; platelet factor 4 levels and beta-thromboglobulin levels are markers of general platelet reactivity and release and are usually elevated in DIC patients. Several reports have suggested that either of these markers may be worthwhile in DIC and for monitoring efficacy of therapy of the intravascular clotting process (149,150). Both assays are readily available for the clinical laboratory, and each has attendant advantages and disadvantages.…”
Section: Molecular Markers For the Diagnosis Of Dicmentioning
confidence: 99%